Different Chemical Composition of Aggregate Impact on Hydraulic Concrete Interfacial Transition Zone - Shi, Yan; Dong, Yun; Wang, Lei; Chen, Xia; Li, Xiang (Asian Journal of Chemistry, 2014)
Based on testing technology of SEM/EDS, microcosmic interfacial transition zone structure of hydraulic concrete of different aggregates were studied, such as limestone, basalt and sandstone. The results showed that used different aggregates in concrete, there were differences in element distribution and variation along the designated path in interfacial transition zone, as well as interface width. Enrichment of Ca(OH)2 in interfacial transition zone was affected by chemical and physical properties of aggregates, such as chemical composition and water absorption. The Ca(OH)2 enrichment degree and interface width were ordered, respectively as follow: sandstone > basalt > limestone and sandstone > limestone > basalt. Sandstone concrete has the weakest interface structure.